Case Report: Successful Response to Intravenous Immunoglobulin and Steroid Pulses in a Renal Transplant Recipient With Severe Covid-19 Disease and Associated Acute Allograft Failure - Rosa-Guerrero, Pedro; Trujillo-Aguilera, Antonio; Molina, Juan; Navas, Ana; López-Martín, Cristina; Jurado, Aurora; Rodríguez-Benot, Alberto; Torres-De-Rueda, Álvaro (Frontiers in Immunology, 2021)
Abstract The impact of Covid-19 pneumonia caused by SARS-CoV-2 on transplanted populations under chronic immunosuppression seems to be greater than in normal population. Clinical management of the disease, particularly in those patients worsening after a cytokine storm, with or without allograft impairment and using available therapeutic approaches in the absence of specific drugs to fight against the virus, involves a major challenge for physicians. We herein provide evidence of the usefulness of high-dose intravenous immunoglobulin (IVIG) combined with steroid pulses to successfully treat a case of Covid-19 pneumonia in a single-kidney transplanted patient with mechanical ventilation and hemodialysis requirements in the setting of a cytokine storm. A rapid decrease in the serum level of inflammatory cytokines, particularly IL-6, IL-8, TNF-α, MCP-1 and IL-10, as well as of acute-phase reactants such as ferritin, D-dimer and C-reactive protein was observed after the IVIG infusion and methylprednisolone bolus administration with a parallel clinical improvement and progressive allograft function recovery, allowing the patient’s final discharge 29 days after the treatment onset. The immunomodulatory effect of IVIG together with the anti-inflammatory and immunosuppressive potential of steroids could be an alternative strategy to treat severe cases of Covid-19 pneumonia associated with an uncontrolled inflammatory response in transplanted populations.